Model Perhitungan Daya Tampung Beban Pencemaran Air Danau Dan Waduk - Badruddin Macbub (JURNAL SUMBER DAYA AIR, 2010)
Indonesia has various types of lakes and reservoirs. The total number of lakes and reservoirs larger than 10 ha is about 521 with total area 491.724. Ha. Some of the lakes and reservoirs face environmental problems caused by water pollution. However, implementation of water quality management and water pollution control regulations needs calculation of the Pollution Load Carrying Capacity (PLCC) as basis to consider the permitted load. A model to calculate PLCC for lakes or reservoirs was developed and regulated according to the Decree of the Minstry of Environment No. 28, 2009. The author has developed the PLCC model and implement it in two lakes, four reservoirs and five ‘situs’ (very small lake), and has developed also the Lymnoqual version 01 software produced by Ecoterra Multiplan. This model is of zero dimension (completely stired tank model), very simple and practical for quick calculation. Based on the model, pollution load inLindu Lake has to be reduced 60.87% to fulfill the PLCC of 38,297 kg P/year; whereas the Maninaju Lake 74.0% to meet PLCC of 223,375 kg P/year and reducing the total number of fish cages from 10.000 to be 2.000. Reservoirs in West Java need water pollution control to meet the PLCC. The reservoirs Saguling has to reduce the number of fish cages with 48,1% (from 6.980 to 3.621 units), Cirata 85.9% (from 49.985 to 7.037 units), Jatiluhur 57.7% (from 15.810 to 6.692 units), and Darma 71.2% (from 200 to 58 units).